The concept of medicine among five-, seven-, and nine-year old Filipino children - Bergara, Meoni Erika F.; Pernia, Ma. Angelica Bianca; Tongson, Excelsa C. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This study explores the concept of medicine among Filipino children, identifying their sources of information, and describing their knowledge, beliefs and attitudes towards these substances. Through purposive sampling, a total of 30 participants were selected in the chosen schools, 10 children from each age group of five, seven and nine, to gain insights on the three different levels of education: kinder, primary and intermediate. The data for the study were gathered through the use of interview and worksheet, and were analysed through content analysis. Furthermore, the data were subjected to open coding process wherein categories were established based on the targeted objectives. Results show that children learn medicine concepts primarily from their parents but are also taught by other memebers of society such as physicians, teachers, and their other relatives. Children's sources of information increase along with their social interaction. Results also show that younger children identify medicines through physical descriptions and as they grow older, they rely heavily on medicines' generic or brand names. Furthermore, children do not consider medicines' physical appearances and prices as indicators of effectivity. Instead, their personal experiences and sources of information influence their beliefs towards these substances. Generally, children have a positive attitude towards medicine due to its therapeutic power, preventive effect, and even its pleasant taste.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman
Keywords: Child psychology -- Philippines; Medical education -- Philippines; Children -- Philippines -- Attitudes